Formulation of a whey-based beverage supplemented with collagen protein hydrolysate - Gorbacheva Mariya; Zachesova Inessa; Esepenok Konstantin; Zemtsova Lyudmila (BIO Web of Conferences)
Production of enriched foods is one of the priorities of the Russian policy focused on national health. The use of collagen is of strong interest in many sectors of national economy, with food production being no exception. This is due to a variety of its properties. The article deals with the formulation of the enriched whey-based beverage supplemented with collagen protein hydrolysate. The objects of research were experimental variants of formulas of a whey-based beverage resulting from the manufacture of Adyghe cheese with a mass fraction of fat of 45%. The tested samples were added with, g/100 g: collagen protein hydrolysate from 1.5 to 3.5, and honey from 5 to 7. The choice of input raw components has been justified, and the benefits of addition of collagen in the formulation of the whey-based beverage have been demonstrated. It was found that the sample beverage had the most balanced composition and flavour profile with the following component ratio, g/100 g: cheese whey of 91.23; honey of 6.0; pectin of 0.25; collagen protein hydrolysate of 2.5; preservative of 0.02. All variants of the beverage had low energy values, not exceeding 78.6 kcal (330.12 kJ) per 100 g. Due to low content of fat and casein, the beverage can be classified as a dietary product, and the introduction of collagen hydrolysate as an enrichment agent in its formulation increases the biological value of the beverage. Daily consumption of a daily serving (330 ml) of this beverage has been proven to provide 22.57% of the recommended daily intake of protein.